Classificazione, inquadramento diagnostico e trattamento della lesione di Monteggia in età pediatrica - Gallone, G.; Trisolino, G.; Di Gennaro, G.T.; Antonioli, D.; Stilli, S. (Lo Scalpello - Journal, 2018)
CLASSIFICATION, DIAGNOSIS AND TREATMENT OF MONTEGGIA LESIONS DURING CHILDHOOD Monteggia fractures represent the association of a fracture of the proximal ulna and luxation of the radial head. This type of lesion is infrequent and may be misdiagnosed, particularly in paediatric patients. Classification of these injuries is based on the scheme proposed by Bado and later supplemented by other authors to better discriminate doubts and to guide the treatment. The treatment of choice of acute Monteggia lesions in the paediatric age is in most cases conservative, and it involves reduction and immobilisation in a cast. Surgery is mostly reserved for complex cases and for inveterate lesions that represent a high risk for chronic disorders and disabling sequelae; in these cases, the choice of treatment remains controversial. The aim of this article is to describe the anatomical-pathological characteristics, the diagnostic criteria, and the principles of treatment of Monteggia lesions in the paediatric age.